ANALISIS SWOT DALAM PENGEMBANGAN STRATEGI PEMASARAN SANGKAR BURUNG: Studi Kasus Di Desa Dawuhan Mangli Sukowono - Faiqotul Maghfiroh; Pudhak Prasetiyorini, Sri Wulandari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The birdcage industry in Dawuhan Mangli Sukowono Village has deep historical roots and is an integral part of the local cultural heritage. This study aims to assess the dynamics of the sector and design an efficient marketing strategy to strengthen the competitive position of businesses in an increasingly fierce market. The research methodology adopted a combination approach (quantitative and qualitative), with data collection through structured surveys and in-depth interviews with entrepreneurs and relevant stakeholders. To identify strengths, weaknesses, opportunities, and threats (SWOT analysis), data were analyzed using the Internal Factor Evaluation Matrix (IFE) and External Factor Evaluation Matrix (EFE). Research findings indicate that, despite promising market potential, entrepreneurs face constraints such as demand fluctuations and competitive intensity. It is hoped that this research can provide practical recommendations for businesses and related parties in formulating policies that support the progress of the handicraft industry, especially birdcages, in the region.